2006
DOI: 10.1073/pnas.0601992103
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine targets early progenitor cells in the adult brain

Abstract: Chronic treatment with antidepressants increases neurogenesis in the adult hippocampus. This increase in the production of new neurons may be required for the behavioral effects of antidepressants. However, it is not known which class of cells within the neuronal differentiation cascade is targeted by the drugs. We have generated a reporter mouse line, which allows identification and classification of early neuronal progenitors. It also allows accurate quantitation of changes induced by neurogenic agents in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
533
4
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 566 publications
(577 citation statements)
references
References 28 publications
31
533
4
9
Order By: Relevance
“…Growth factors act via MAPK signaling to induce the transcription of IEGs and transcription factors that promote the proliferation of neuronal progenitor cells and the survival and differentiation of newly born neurons. A recent study has identified a specific class of neuronal precursor cells, amplifying neural progenitors that appear to be sensitive to chronic fluoxetine treatment (Encinas et al, 2006); it is possible that the straindependent effect of fluoxetine on neurogenesis is due to genetic polymorphisms associated with this type of cell.…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors act via MAPK signaling to induce the transcription of IEGs and transcription factors that promote the proliferation of neuronal progenitor cells and the survival and differentiation of newly born neurons. A recent study has identified a specific class of neuronal precursor cells, amplifying neural progenitors that appear to be sensitive to chronic fluoxetine treatment (Encinas et al, 2006); it is possible that the straindependent effect of fluoxetine on neurogenesis is due to genetic polymorphisms associated with this type of cell.…”
Section: Discussionmentioning
confidence: 99%
“…Since rolipram plays its role in neurogenesis via activation of the cAMP/CREB cascade, neurogenesis induced by PDE4B deficiency likely is also mediated by cAMP signaling. Interestingly, chronic administration of the antidepressant fluoxetine, a selective serotonin reuptake inhibitor, not only increases hippocampal neurogenesis (Encinas et al, 2006;Malberg et al, 2000), but also decreases the expression of PDE4B in the brains of mice and rats (Dlaboga et al, 2006;Miro et al, 2002). However, while these findings appear to be consistent with FST behavior and hippocampal neurogenesis observed in PDE4BÀ/À mice, further studies are needed to determine their relationship to antidepressant activity.…”
Section: Pde4b-deficiency and Behavior H-t Zhang Et Almentioning
confidence: 98%
“…7). Previous works have demonstrated that cell cycle regulation in the adult brain is precursor-type-specific [24], thus we sought to determine whether the defect in proliferation observed in Cdk6 À/À brains was restricted to a subpopulation versus all cycling precursors. First, we used glial fibrillary acidic protein (GFAP) and the Sry-related HMG box transcription factor Sox2 to identify immature DG precursors with, respectively, radial (type 1) and nonradial (type 2a) morphology that are not yet restricted to a neuronal fate [25].…”
Section: Cdk6 Selectively Regulates the Proliferation Of Neuronally Cmentioning
confidence: 99%